2009
DOI: 10.3354/meps08098
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation in Hong Kong waters inferred from comparison of nutrient ratios, bioassays and 33P turnover times

Abstract: There is a need to determine the spatial and temporal dynamics of nutrient limitation to decide which nutrients should be removed during sewage treatment in Hong Kong. We compared 3 methods to assess potential or actual nutrient limitation. Ambient nutrient ratios were calculated, and nutrient enrichment bioassays were conducted, along with 33 P turnover times. Comparison of nutrient ratios and bioassays demonstrated that the ambient inorganic nutrient ratios, based on the Redfield Si:N:P ratio of 16:16:1, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 55 publications
(91 reference statements)
3
30
0
Order By: Relevance
“…In the outer bay, the high flushing rate was likely responsible for low phytoplankton biomass (Lee and Qian 2003). The influence of physical processes on the regulation of phytoplankton growth was also observed in the nearby western waters of Hong Kong (Xu et al 2008(Xu et al , 2009). …”
Section: Discussionmentioning
confidence: 90%
“…In the outer bay, the high flushing rate was likely responsible for low phytoplankton biomass (Lee and Qian 2003). The influence of physical processes on the regulation of phytoplankton growth was also observed in the nearby western waters of Hong Kong (Xu et al 2008(Xu et al , 2009). …”
Section: Discussionmentioning
confidence: 90%
“…The contrast between high chl a-specific photosynthetic rates observed in the incubation experiments and the low in situ chl a concentrations in spring suggested that the processes (e.g., dilution, mesozooplankton grazing, and vertical mixing) that were excluded in the incubation experiments were the primary factors that were responsible for the relatively low in situ chl a concentrations. This suggestion was supported by a series of simultaneous nutrient enrichment bioassays, which showed that the ambient nutrients could support algal growth for a few days, and the algal biomass increased several times when dilution and vertical mixing were reduced in the bottle incubations (Xu et al 2009). …”
Section: Temporal Variabilitymentioning
confidence: 82%
“…In addition, the Pearl River discharge might transport phytoplankton into southern waters and partially contribute to the high algal biomass in southern waters. An unusually large summer bloom (up to 73 μg chl L −1 ) was observed in this region (Stn S12), accompanied by a drawdown of PO 4 to limiting concentrations (Xu et al 2009). The frontal region of the plume has also been found to have high chl a concentrations relative to inshore and offshore waters in other coastal waters such as Chesapeake Bay (Breitburg 1990;Harding 1994) and the Mississippi River plume (Grimes and Finucane 1991).…”
Section: Spatial Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Port Shelter is a sheltered water body relatively far away from anthropogenic pollutions and the influence from a large river-the Pearl River west of Hong Kong. Its hydrology and chemistry background has been extensively studied (Yung et al 2001;Xu et al 2009). Owing to the influence of China coast current, the nutrient concentrations are usually elevated during the wintertime in Port Shelter (Yin 2003;Chen et al 2009).…”
Section: Introductionmentioning
confidence: 99%